Isolated limb perfusion - Hočevar, Marko (Onkologija : Slovenian Journal of Oncology, 2010)
Isolated limb perfusion (ILP) is a form of regional treatment of locally advanced limb cancers. It was first described in 1950s and modified with time. In 1980s, hyperthermia was added and in 1990s TNF (tumor necrosis factor). ILP is indicated in the patients with locoregionally advanced melanoma (in transit metastases) and in the patients with limb sarcomas where amputation would be the only radical treatment. During the procedure, the artery and vein for lower/upper limb is isolated and connected to the heart-lung machine. In the first part of the procedure, the isolated limb is warming to about 40o C and leakage measurements with isotope are performed. If there is no leakage, cytotoxic drug is applied in the dosage 10-20 times higher than the maximal dosages during systemic application. At the end of the procedure, the limb is washed out and the vessels repaired. Postoperative complications are usually regional in the form of erythema and edema. ILP is an effective treatment with complete response rates reaching 70% in patients with melanoma and 80% limb sparing in patients with advanced sarcomas.